Fictive Deixis, Direct Discourse, and Viewpoint Networks - Dancygier, Barbara (Frontiers in Communication, 2021)
This article considers three linguistic categories – deixis, direct discourse and viewpoint. These concepts are often discussed separately, in spite of important correlations in meaning and usage. I discuss a range of non-standard examples to demonstrate how the categories overlap and/or condition each other in discourse. Specifically, I consider examples from strikingly different genres to show their reliance on deixis, their use of direct speech, and the resulting viewpoint phenomena. I look at the literary genres (fiction, poetry and drama), internet memes, and storefront signs, to demonstrate the important ways in which they rely on, but also change, the understanding of deixis. My look at these genres is, of necessity, selective, as I focus on expressions structured as direct discourse which depend on a fictive (and/or incomplete) deictic centre. To explain the nature of the usage across the genres selected, I propose the category of fictive deixis, and relate it to processes of perspectivization. Importantly, the inclusion of visual and multimodal artifacts provides added evidence for the nature of viewpoint construction in expressions based on fictive deixis and formal signals of direct discourse.